Reactions of nitric oxide on Rh6+ clusters: abundant chemistry and evidence of structural isomers. - Ford, MS; Anderson, M; Barrow, M; Woodruff, D; Drewello, T; Derrick, P; Mackenzie, S (2005)
We report the first results of a new instrument for the study of the reactions of naked metal cluster ions using techniques developed by Professor Bondybey to whom this issue is dedicated. Rh6+ ions have been produced using a laser vaporization source and injected into a 3 T Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer where they are exposed to a low pressure (< 10(-8) mbar) of nitric oxide, NO. This system exhibits abundant chemistry, the first stages of which we interpret as involving the dissociative chemisorption of multiple NO molecules, followed by the liberation of molecular nitrogen. This yields key intermediates such as [Rh6O2]+ and [Rh6O4]+. The formation of the latter, after adsorption of four NO molecules, marks a change in the chemistry observed with further NO molecules adsorbed (presumably molecularly) without further N2 evolution until saturation is apparently reached with the [Rh6O4(NO)7]+ species. We analyse the data in terms of a simple 12-stage reaction mechanism, and we report the relative rate constants for each step. The trends in reactivity are assessed in terms of conceivable structures and the results are discussed where appropriate by comparison with extended surface studies of the same system. Particular attention is paid to the first step in the reaction (Rh6(+) + NO --> [Rh6NO]+) which exhibits distinctly bi-exponential kinetics, an observation we interpret as evidence for two different structural isomers of the Rh6+ cluster with one reacting more than an order of magnitude faster than the other.